An Observational Study on Treatments Used in Orthopaedic Patients - Saivineesha, Yeluru; Lingaiah, Mahadevamma; Radhakrishna, Tejaswini; Paul, Diptanu; H, Sharath Chandra (Journal of Pharmacy Practice and Community Medicine)
Objectives: This research aimed to assess and evaluate pharmacotherapy and nonpharmacotherapy treatments in orthopaedic disorders. Methods: This was a prospective and observational study which was performed on 122 subjects in the orthopaedic department. Study was assessed and evaluated by suitable statistical tools. Results: The maximum age distribution seen was more than 50 years old. Most of the subjects diagnosed with 34.5% of arthritis with frequently prescribed drugs were analgesics, opioid’s, NSAID’s, anti-inflammatory, calcium supplements, Vitamin and mineral supplements. In this treatment, non-pharmacotherapy was advised along with pharmacotherapy. Among 122 subjects, 85.2% were shown to have “Recovered”, in which a 71.3% recovery rate was observed with adherence to both pharmacotherapy and non-pharmacotherapy compared with individual therapies. In this study, 142 potential drug-drug interactions were monitored with their comorbidity conditions. Conclusion: The study reveals that due to an increase in age, changes in lifestyle habits lead to more bone-related problems, which further lead to difficulty in doing their daily activities. The majority of issues in orthopaedic management include both pharmacotherapy and nonpharmacotherapy. Therefore, it is necessary to adhere to both treatments to improve the quality of life and daily living. We can reduce the incidence rate by advising people to do regular exercise with a balanced diet, exposure to sunlight which helps to strengthen the bones and muscles.
Keywords: Orthopaedic; Pharmacotherapy; Non-pharmacotherapy; Adherence; Drug interactions; Comorbidities